Biosynthesis and Characterization of Iron Nanoparticles Using Pseudomonas and Actinobacteria - Nazma, S.; Sudha, T.; Biradar, D. P.; Krishnaraj, P. U.; Chandrashekhar, S. S.; Ravikumar, H. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was carried out during 2022 to study on the biosynthesis and characterization of iron nanoparticles in the Green Nanotechnology Laboratory, University of Agricultural Sciences, Dharwad, Karnataka, India. Collection and screening of Pseudomonas and actinobacterial isolates were done at the Microbial Genetics Laboratory, Department of Agricultural Microbiology of the university and the iron nanoparticles were biosynthesized and characterized through UV-Visible spectroscopy, Particle Size Analyzer (PSA), Scanning Electron Microscope (SEM), (EDX), X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). The formation of the FeNPs was preliminary confirmed by the change in the colour of the reactant mixture visually by monitoring the change in colour from orange to black colour. The iron nanoparticles (FeNPs) synthesized through AUDP209 (Pseudomonas) and AUDT636 (actinobacteria) exhibited peak values at 294 and 297 nm, with average sizes of 51.7, and 58.0 nm, respectively. SEM images revealed the spherical shape of the biosynthesized iron nanoparticles (FeNPs), while EDX confirmed the iron ions presence in the biosynthesized samples and the crystalline structure of the iron nanoparticles was confirmed by XRD. FeNPs biosynthesized through AUDP209 showed the absorption peaks at 2337 cm-1, 1639 cm-1, 1118 cm-1, 794 cm-1, 540 cm-1 and FeNPs biosynthesized through AUDT636 showed the absorption peaks at 3741 cm-1, 2349 cm-1, 2067 cm-1, 964 cm-1, 551 cm-1. FTIR spectroscopy confirmed the organic compounds present in the microbial extracts responsible for the capping and stabilizing agents for biosynthesis of FeNPs.